Synthesis, characterisation and biological activities of novel nitrogen-sulphur macrocyclic ligands and their transition metal complexes - Chah, Chee Keong (2017)
Macrocycles have a great importance in macrocyclic and supramolecular chemistry. The term macrocycle is defined as a cyclic macromolecule with more than eight members. Macrocyclic Schiff bases and their transition metal complexes have various interesting biological properties such as cytotoxic, DNA binding, and antibacterial activities. In this project, the first novelty was the synthesis of five series tetradentate nitrogen-sulphur macrocyclic Schiff base derived from terephthaloyl-bis-dithiocarbazate (TDTC) using glyoxal (G), 2,5-hexanedione (H), acetyl acetone (A), 5,5-dimethyl-1,3-cyclohexanedione (D), and malondialdehyde (M). Their complexes were formed via reaction with various metal acetate or metal chloride salt [Ni(II), Cu(II), Zn(II), Cd(II), Nb(II), Ru(III), Mo(V), and Pd(II)]. A total of 40 metal complexes were synthesised and these complexes were expected to have a general formula of M2L or M3L. These compounds were characterised by various physico-chemical and spectroscopic techniques. Based on the data obtained, the azomethine nitrogen atom and the thiolate sulphur atom from the Schiff base were coordinated to the metal ions. The geometry of Cu(II), Nb(II) and Pd(II) complexes was distorted square planar, but the Ni(II), Zn(II), Cd(II) and Ru(III) complexes was distorted square pyramidal. The Mo(V) complexes showed a distorted pentagonal bipyramidal. The Schiff bases and their metal complexes were evaluated for their cytotoxic activities against the invasive human bladder carcinoma cell line (EJ-28) and the minimum-invasive human bladder carcinoma cell line (RT-112). MTT assay was used in the determination of IC50 values. From the data obtained, the macrocyclic Schiff bases were inactive against to both the bladder cancer cell lines but the respective complexes had significantly increased cytotoxic activity. The complexes also showed higher activity against RT-112 than EJ-28. The IC50 for PdTGSB and RuTGSB complexes against RT-112 were strongly active with the values of 0.320 and 0.472 μM, respectively. The second novelty in this study was the mechanism of death assays using macrocyclic compounds. The two active complexes were further studied for the mechanism of death via Reactive Oxygen Species (ROS) and Annexin V assays. Migration assay was also carried out on the most inactive compound, which was CuTGSB. The DNA binding interaction of the complexes with calf-thymus DNA (CT-DNA) was investigated via electronic absorption spectroscopy, fluorescence spectroscopy, and viscosity measurements. The binding constant, Kb for PdTGSB was 3.79 x 104 M-1 and the binding mode was electrostatic binding. Antibacterial studies using three Gram-positive (B. cereus, S. aureus, Methicillin-resistant S. aureus) and four Gram-negative (E. coli, K. pneumonia, S. typhimurium, S. sonnei) bacteria were carried out. Standard disc diffusion method and determination of minimum inhibitory concentration (MIC) were used in the antibacterial studies. The macrocyclic complexes were generally more active against the Gram-positive bacteria as compared to the Gram-negative bacteria. The MIC values obtained for CdTHSB and CdTASB against B. cereus was 2.0 mg/mL. Hence, these complexes were the candidates to be antibacterial agents.